2020
DOI: 10.1111/hiv.13027
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor chidamide induces intermittent viraemia in HIV‐infected patients on suppressive antiretroviral therapy

Abstract: Objectives To evaluate the safety and efficacy of chidamide to reverse HIV‐1 latency in vivo and to compare the effects of four clinically tested histone deacetylase (HDAC) inhibitors on non‐histone proteins in vitro. Methods Participants received chidamide orally at 10 mg twice weekly for 4 weeks while maintaining baseline antiretroviral therapy. The primary outcome was plasma viral rebound during chidamide dosing and the secondary outcomes were safety, pharmacokinetic and pharmacodynamic profiles, changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In the context of HIV-1 infection, chidamide can reactivate the latent viral reservoir through NF-κB signaling. It is a safe treatment option and can induce intermittent viremia in HIV-1 positive patients and, beyond that, a modest decrease in viral DNA [ 114 , 115 ]. Based on chidamide’s and entinostat’s ability to reactivate HIV-1 from latency, these agents should be further evaluated in the context of HTLV-1 latency reversal.…”
Section: Manipulation Of Histone Modificationmentioning
confidence: 99%
“…In the context of HIV-1 infection, chidamide can reactivate the latent viral reservoir through NF-κB signaling. It is a safe treatment option and can induce intermittent viremia in HIV-1 positive patients and, beyond that, a modest decrease in viral DNA [ 114 , 115 ]. Based on chidamide’s and entinostat’s ability to reactivate HIV-1 from latency, these agents should be further evaluated in the context of HTLV-1 latency reversal.…”
Section: Manipulation Of Histone Modificationmentioning
confidence: 99%
“…Tucidinostat, a novel and orally active benzamide class of HDAC inhibitor, exhibited high potency for the treatment of cancer and non-cancer diseases, such as the common autoimmune bleeding disorder ITP and AIDS as an antiretroviral therapy (Schmiegelow, 2019;Zhao et al, 2019;Li et al, 2020). In the cancer field, tucidinostat is currently being evaluated in many clinical trials with the most advanced research progress being in the field of hematological malignancies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition, this class of LRAs has demonstrated an acceptable tolerability in cART-treated individuals infected with HIV-1. However, to date, even if some HDACis could increase HIV production in vivo, clinical trials using HDACis alone have shown no or only a modest decrease in viral reservoir size (35)(36)(37)(38), presumably because the degree of latency reversal was limited and/or the immune system was not primed to clear antigen-expressing cells (27). These results underline the importance of testing combination LRA treatments in order to address the multifactorial and heterogeneous nature of HIV-1 latency (as discussed in the section titled Latency Reversing Agent Combination Therapy) (23).…”
Section: Epigenetic Latency Reversing Agentsmentioning
confidence: 99%